Diversity and abundance of nematodes in soil treated with solarization treatments - Astri Harnov Putri; Siwi Indarti; Tri Harjaka (Society for Indonesian Biodiversity, 2021)
Abstract. Putri A H, Indarti S, Harjaka T. 2021. Diversity and abundance of nematodes in soil treated with solarization treatments. Biodiversitas 22: 2612-2618. Solarization is a tillage cultivation technique that influences the presence of nematodes in agricultural land. This research aims to determine the solarization effect on soil temperature and nematode abundance and diversity in the soil. Observations on species, diversity, and abundance of the nematodes were performed at the Nematology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Gadjah Mada University. A completely randomized design (CRD) was used with six treatments and three replications. Meanwhile, the treatment groups were based on solarization duration (in days) on the soil which includes A(3), B(7), C(14) D (30), and K0 (control, without solarization) and K1 ( control, farmer treatment). Field observations were performed to measure soil temperature, moisture, and pH. Nematodes were analyzed in the laboratory to determine the genus, abundance, and diversity. Furthermore, extracted plant-parasitic nematodes were isolated by using the whitehead tray method while the entomopathogenic group was isolated using the baiting method. The results showed the differences in tillage treatment and solarization affect soil temperature (diversity and abundance). A polynomial regression model explained the relationship between increased solarization time and soil temperature. The highest soil temperature was found in cultivated land and solarization land for 14 days (41.0oC) and the lowest was in the treatment of farmers (33.67oC). The lowest abundance was found at 14 days solarization, namely 286 individuals/100g, and the diversity index value of 1.37. The highest diversity index was found in the treatment of farmers with an index value of 1.75. The solarization treatment is best applied in the field for 14 days.